(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Vehicular ad-hoc network (VANET) is an eminent component of intelligent transportation systems. VANET offers communication between moving vehicles on the road and the road-side objects using wireless network. Nowadays, automobile manufacturers have embedded numerous applications of VANET in vehicles for a safer and entertaining journey. Due to the frequent disconnection property of VANET, it is necessary to improve vehicular connectivity. To facilitate the dissemination of important and time-sensitive messages, network connectivity between vehicles are of great importance. To determine connectivity duration (CD) in a probabilistic manner, an analytical model is proposed in this study. The model makes the use of various factors, including transmission range, node density, vehicle spacing density, safety distance, road length and size of the cell. The CD is determined for the one-lane road segment in VANET. The impact of transmission range, road segment length and safety distance on vehicular connectivity is measured. The influence of safety distance between neighboring vehicles on CD probability is also evaluated. The result shows that 3% better connectivity is achieved in the road segment having a high transmission range. In case of safety distance, 68% better vehicular connectivity for the road segment that has a high transmission range.